Reproductive Biology of Rasbora cephalotaenia from the Kandis River, Karya Indah Village, Tapung District, Kampar Regency, Riau - Widiana, Mita; Eddiwan, Eddiwan; Efawani, Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTRasbora cephalotaenia is found in the Kandis River. A study aims to understand the reproductive biology of R. cephalotaenia has been conducted on March - May 2018. The fish was sampled 4 times , once/ 2 weeks. Parameters measured were sex ratio, gonad maturity level, Gonad Somatic Index (GSI), fecundity and egg diameter. Results shown that there was 75 males and 53 females (sex ratio 2:1). Size at maturity level in male ranged from 57.49 mm SL, while that of the females was 69.24 mm SL. The average of male’s GSI ranged from 4.75 - 7.06%, while that of the females was 7.02 - 13.73%. The average of fecundity was 2,416 eggs and egg diameter was 0.28 - 0.56 mm. Based on the size and distribution of egg diameter, it can be concluded that this fish is a partial spawner. Keywords: Sex ratio, gonad maturity level, gonad somatic index, total spawner